A promising strategy for conservation of endemic plant Euonymus koopmannii - NURTAI GUBAIDULLIN; BALNUR KALI; DILNUR TUSSIPKAN; SHUGA A. MANABAYEVA (Society for Indonesian Biodiversity, 2024)
Abstract. Gubaidullin N, Kali B, Tussipkan D, Manabayeva SA. 2024. A promising strategy for conservation of Central Asian endemic plant Euonymus koopmannii. Biodiversitas 25: 3114-3120. Cryopreservation of endemic plants is necessary to safeguard the biodiversity and genetic resources of unique species that may face extinction due to climate change or human activities. This process enables the long-term preservation of their genetic information and ensures the possibility of restoring these species. Euonymus koopmannii Lauche is, known as E. nanus var. turkestanicus, is a native to Kazakhstan and other Central Asian countries. The E. koopmannii is listed in the Red Book of Kazakhstan and has ecological importance in soil stabilization and its decorative value. This study aims to contribute to the conservation efforts of E. koopmannii by establishing an effective cryopreservation protocol for its meristems. This study has identified for the first time an optimized cryopreservation protocol for E. koopmannii meristems involving specific treatment durations and osmotic solutions. The protocol resulted in a significantly higher survival rate (60%) when meristems were precultured with 0.3 M sucrose, treated with Plant Vitrification Solution 2 for 30 min., and regenerated on a medium with 20 g/L sucrose. Secondly, a comparative analysis of cryopreserved regenerates with a control group has revealed that cryopreservation negatively impacted the plant height but significantly increased the number of meristem shoots and roots. This finding highlights the trade-off between growth and root development in cryopreserved plants. Thirdly, the presented optimization of the cryopreservation protocol provides valuable insights for the preservation and regeneration of E. koopmannii meristems. It emphasizes the critical importance of precise treatments and the composition of the nutrient medium to achieve successful cryopreservation and subsequent recovery of plants in tissue culture. This research provides essential information for conserving E. koopmannii, shedding light on the intricate balance required to apply cryopreservation techniques effectively.